The formal and informal caregivers: comparative analysis between the family and institucional contexts - Queirós, Telma Maria Gonçalves (2014)
Population aging has become an emerging problem in society. The combination of several factors led to an increase in life expectancy, which is reflected in a number of people with a more advanced age and therefore more dependent. Thus, this led to greater demands for formal and informal support. In this sense, with this study we aimed to (i) know the type of care which are provided to the older people, by Formal and Informal Caregivers; (ii) understand the perspective of Formal and Informal Caregivers about the care provided, in family and institutional contexts; (iii) identify the main difficulties involved in providing care for the Formal and Informal Caregivers and (iv) identify the support (e.g. social, technical) that are delivered to the caregivers. This study used two questionnaire surveys. A survey consisting of thirteen closed questions was applied to ten Formal Caregivers (FCs), employees of a Private Institution of Social Solidarity, in a city of the north of Portugal. Both were female, aged between 20-59 years. The second survey consisted of fourteen closed questions and was applied also to ten Informal Caregivers (ICs), living in the rural area of the same city. Nine were female and one was male, aged between 40-65 years. A comparative statistical analysis was used. Results had show that the FCs provides social and physical care, while the ICs provide emotional and physical care. Participants consider as priority care, physiological, psychological and social care. FCs appointed two reasons to exercise this function: like to work with older people and like to feel competent. For the ICs, the reasons are being familiars of the elderly and therefore feel they have the obligation and duty to exercise that function. Both indicated that the main difficulty is the physical fatigue. Moreover, the FCs point to a lack of cooperation from the elderly and ICs indicate the lack of housing conditions and technical support. Despite these issues, they consider institutionalization as an alternative. They believe that the elderly are satisfied with the care provided.